Exports, imports, exchange rates, gross domestic investment and growth: Empirical evidence from Cameroon - Yusoff, Mohammed; Nulambeh, Ndzembanteh Aboubakary (IIARD Publishing (International Institute of Academic Research and Development), 2016)
The main objective of this study is to investigate whether exports, imports, exchange rates, and gross domestic investment are important in determining economic growth in Cameroon. The Johansen tests of co-integration suggest the presence of a long-run relationship among the variables and all the long-run coefficients have the expected signs and significant at least at 5% level. Specifically, exports, gross domestic investment, and exchange rate positively influence economic growth of Cameroon while the impact of imports on GDP growth is negative; a 1% increase in exports and gross domestic investment increases GDP by approximately 2.4% and 4.5% respectively, while 1% depreciation in Cameroon currency improves the GDP by 2.6% in the long run. Finally, a 1% increase in imports will decrease the GDP of Cameroon by 8% in the long term. The results of Granger causality tests indicate that exports, investment, and imports cause GDP growth in the short-run unidirectional, but bidirectional causality exists between exports and imports. The variance decomposition results suggest that in the 20th period horizon, the variation in GDP growth is explained by exports at 41.64%, imports at 19.64 %, gross domestic investment at 17.98 % and exchange rate at 15.02 5 suggesting that economic growth in Cameroon has been spearheaded by exports, followed by gross domestic investment, and exchange rate. Imports have negative impact on growth suggesting that, perhaps, most of the imported goods are consumption goods rather than capital goods or intermediate goods.